Effect of susceptible and resistant canola plants on Plasmodiophora brassicae resting spore populations in the soil. (25th May 2012) - Hwang, S. F.; Ahmed, H. U.; Zhou, Q.; Rashid, A.; Strelkov, S. E.; Gossen, B. D.; Peng, G.; Turnbull, G. D.
<x xml:space="preserve">Abstract</x> Clubroot, caused by Plasmodiophora brassicae, has become a serious threat to canola (Brassica napus) production in western Canada. Experiments were conducted to assess the effect of growing resistant and susceptible canola genotypes on P. brassicae soil resting spore populations under greenhouse, mini‐plot and field conditions. One crop of susceptible canola contributed 1·4 × 108 spores mL−1 soil in mini‐plot experiments, and 1 × 1010 spores g−1 gall under field conditions. Repeated cropping of susceptible canola resulted in greater gall mass compared to resistant canola lines. It also resulted in reduced plant height, increased clubroot severity in susceptible canola, and increased numbers of resting spores in the soil mix.